Cosec observers during the trial of the EFEE, in connection with the mass demonstration against the assasination of Lambrakis. Eckstein on the right - Tassos, Anastasios Meïmaroglou
Cosec observers during the trial of the EFEE, in connection with the mass demonstration against the assasination of Lambrakis. Eckstein on the right.